If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12(n+1)-11n+2(n+1)=56
We simplify the equation to the form, which is simple to understand
12(n+1)-11n+2(n+1)=56
Reorder the terms in parentheses
+(+12n+12)-11n+2*(n+1)=56
Remove unnecessary parentheses
+12n+12-11n+2+*(+n+1+)=+56
Reorder the terms in parentheses
+12n+12-11n+(+2n+2)=56
Remove unnecessary parentheses
+12n+12-11n+2n+2=+56
We move all terms containing n to the left and all other terms to the right.
+12n-11n+2n=+56-12-2
We simplify left and right side of the equation.
+3n=+42
We divide both sides of the equation by 3 to get n.
n=14
| 9x-7xy-6= | | x^4+2x^3+2x^2-3x-2=0 | | R=2pirh | | 0+a=a | | 7x+65/89 | | 20-5x-8xy= | | x^2+2x=16384 | | y=x^2+3x+18 | | t^2-162=0 | | 9p=6p | | x^2+3x=2187 | | y=-.4x | | -8p=-3/4 | | 2x+1=6x+9 | | 1.4x=12 | | t=-5x+3y | | 5=3y+2x | | 0.07t=0.77 | | 42-2x=36 | | h-48=17h+42 | | 97x-104=47x+2046 | | 4x+4y=-4 | | 3r^2=22r+16 | | -3x+12=-7x+62 | | 3(-x-1)=11 | | 3/4x4/6 | | 5n-3n+6+n+4n=3 | | 4y+7z=13 | | 14x+17=9x+22 | | 2y=-4x-18 | | 11m+2-m+1+5m= | | 5x+4=x+5 |